Redesain Area Outdoor Gym dan Children Playground pada Lapangan Niti Mandala Renon, Denpasar - Shafira Balqish; Naniek Kohdrata; I Made Agus Dharmadiatmika (Fakultas Pertanian, Universitas Udayana, 2023)
This research aims to make a design as reference to restore the function of children's playground and create a suitable design for the outdoor gym and children's playground area with survey method and proceed with qualitative descriptive analysis which refers to stages of design landscape process by Seymour M. Gold. The result of this research is that the researcher makes a concept design that lead to schematic design based on the result of analytic and synthesis stage. The main concept design refers to the basic form of Museum Bajra Sandhi based on AjiBlêgodawa text then it transformed into design layout of the space that divide into two main space, children’s playground area and outdoor gym area with the mixed circulation path from three types of circulation namely direct circulation, rotating circulation, and collecting circulation. As for the concept facilities, Children’s Playground refers to urban playground concept by utilizing the site as a semi-massive area to give the sense of space exploration for the users, meanwhile the sports facilities refers to cross-fit gym concept to make it more accessible for all. As for the softscape the researcher only use shrubs as an accent and a supporting aspect because this area is already surrounded by large trees.